PENERAPAN METODE CERTAINTY FACTOR PADA SISTEM PAKAR DIAGNOSIS PENYAKIT DAN HAMA TANAMAN MANGGIS - Farha Fitrahul Janah; Gibtha Fitri Laxmi; Freza Riana (Universitas Widyatama, 2021)
Mangosteen is one of the horticultural commodities of Indonesian original tropical fruits and has either high value or prospects for cultivation. One of the obstacles in mangosteen cultivation is the low quality of the fruit caused by pests. In general, one of the efforts to prevent and control the spread of diseases and pests in mangosteen plants is to consult with the expert, however this can be an obstacle due to the limited number of experts in an area. Referring to this problem, in this study, a website-based expert system was created to diagnose diseases and pests in mangosteen plants by applying the Certainty Factor method. There were 5 diseases and 5 pests with 42 symptoms, including 25 symptoms of diseases and 17 symptoms of pests that can be identified by this expert system. The percentage value obtained was 80% for the comparison between expert diagnoses and system diagnoses using the Certainty Factor method. This value was obtained based on the suitability of 50 test data that were randomly generated. This expert system can helps mangosteen farmers and the community in diagnosing diseases and pests in mangosteen plants.